1993
DOI: 10.1523/jneurosci.13-03-01010.1993
|View full text |Cite
|
Sign up to set email alerts
|

Pairing the cholinergic agonist carbachol with patterned Schaffer collateral stimulation initiates protein synthesis in hippocampal CA1 pyramidal cell dendrites via a muscarinic, NMDA-dependent mechanism

Abstract: Effects of afferent stimulation on local synthesis of protein in CA1 pyramidal cell dendrites were studied using light microscope autoradiography. Tissue was fixed with paraformaldehyde immediately after 3 min exposure to 3H-leucine in order to trap 3H associated with macromolecules. The rate of 3H-leucine incorporation into dendrites of resting hippocampal slices was 10% the rate of incorporation into cell somata. Ninety percent of the incorporation into the somata was inhibited by cycloheximide (300 microM);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(80 citation statements)
references
References 44 publications
4
76
0
Order By: Relevance
“…In fact, a late phase protein-synthesis-dependent LTD in hippocampal slice cultures has been reported (25). Nevertheless, we cannot rule out the possibility that LTD induced by concurrent application of Sp-cAMPS and picrotoxin may include an early phase of LTD that requires protein synthesis, presumably locally and within 30 min after the drug treatment (26)(27)(28).…”
Section: Discussionmentioning
confidence: 89%
“…In fact, a late phase protein-synthesis-dependent LTD in hippocampal slice cultures has been reported (25). Nevertheless, we cannot rule out the possibility that LTD induced by concurrent application of Sp-cAMPS and picrotoxin may include an early phase of LTD that requires protein synthesis, presumably locally and within 30 min after the drug treatment (26)(27)(28).…”
Section: Discussionmentioning
confidence: 89%
“…Recently, it has been found that such dendritic protein synthesis may be activated by afferent stimulation: 3H-leucine incorporation in CA1 dendrites is induced immediately after high frequency, but not low frequency, stimulation of Schaffer collaterals in the presence of carbachol (Feig and Lipton, 1993); label incorporation is blocked by D-aminophosphonovalerate and also by atropine.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the induction of LTP at Schaffer collateral-CA1 synapses induced the synthesis of secretory proteins (Duffy et al 1981;Lauri et al 1996). In addition, lowfrequency (10 Hz) stimulation of hippocampal slices treated with the cholinergic agonist carbachol can induce new protein synthesis in dendrites (Feig & Lipton 1993). In synaptosome preparations, glutamate treatment leads to polyribosome formation and translation activation (Weiler & Greenough 1993;Bagni et al 2000).…”
Section: Regulation Of Dendritic Protein Synthesismentioning
confidence: 99%